METODE PEMBELAJARAN BERBASIS AL-QUR’AN - Moh Aman (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2020)
Learning is not just a transformation of knowledge, but more than that the learning process requires the right method so that learning objectives can be achieved. The learning method is a very important component in the learning process, because the learning objectives are achieved or not depending on the learning method applied. Al-Qur'an as a life guide for mankind offers varied learning methods, many verses in the Koran are closely related to learning methods, including the amtsal method, qishshah, khiwar, targhib wa tarhib, tajribah, uswah, ibrah, mau'idhah and others. With the variety of learning methods offered by the Qur'an, it can be used as a learning resource and then implemented in a learning process tailored to the level of education. With this varied learning method, it will be able to avoid the indoctrinal and monotonous learning process which will cause boredom for students.